"Do they fit together like the Joker and Harley Quinn?": Joking, laughing, humor styles, and dyadic adjustment among people in long-term romantic relationships. (December 2022) - Jach, Łukasz; Kubicius, Dominika; Jonason, Peter K.
Abstract: While people value a good sense of humor in their potential romantic partners, we know comparatively less about the function of humor in long-term relationships. Using the survey method, we measured the production, appreciation, and quality of humor along with humor styles and dyadic adjustment in long-term relationships among 149 heterosexual couples. Men produced more jokes than women, but the sexes responded to their partners' jokes at the same frequency. Men also rated their jokes as funnier than the jokes of their partners. Partners were matched in aggressive and self-defeating humor styles. Laughing and humor quality ratings as well as humor styles had effects for men's and women's dyadic adjustment. We conclude that in long-term, romantic relationships, a sense of humor is part of the mechanisms involved in building relationships. Highlights: In long-term relationships, men produce more jokes than women. Men rate their jokes as funnier than the jokes of their partners. Men use more aggressive and self-enhancing humor styles than women. Aggressive and self-defeating humor correlate between members of the couple. Joking, laughing, humor ratings and humor styles had effects for dyadic adjustment.